EFFECT OF MARKETING COMMUNICATION ON BRAND EQUITY AND PATIENT DECISIONS CHOOSING OBSTETRIC AND GYNECOLOGY SERVICES AT RSI HASANAH MOJOKERTO - Nida Urrahmah; Heru Suswojo; Sholihul Absor (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The purpose of this study is to analyze the effect of marketing communication on brand equity and patient decision choosing obstetric and gynecological services at RSI Hasanah Mojokerto. The independent variable in this study is marketing communication, while the dependent variable is the patient decision, and brand equity is a variable mediator between marketing communication and patient decision. The sample of this research were BPJS patients at RSI Hasanah Mojokerto from March to May 2025 who have finished the services of obstetric and gynecological, both outpatient and inpatient. A total of 52 respondents were obtained as samples in this research. This study uses an explanatory survey research design, which involves searching and collecting primary data by directly asking questions to respondents and analyzing the effects among variables to prove the hypothesis. Data analysis using path analysis with SEM-PLS. The results of the study show that the original sample value of the direct relationship between marketing communication and patient decision is +0.101 with a P-value of 0.226. Meanwhile, the original sample values when mediated by brand equity as the mediator variable between marketing communication and patient decision are +0.680 and +0.762 with a P-value of 0.000 at a significance level of 0.05. Thus, it can be concluded that brand equity can act as a mediator between marketing communication and patient decision. With good marketing communication, the brand equity of the Hospital will increase, thereby improving patients' decision choosing obstetric and gynecological services at RSI Hasanah Mojokerto.